2013
DOI: 10.1016/j.jnucmat.2012.09.012
|View full text |Cite
|
Sign up to set email alerts
|

A physically-based correlation of irradiation-induced transition temperature shifts for RPV steels

Abstract: Irradiation embrittlement of reactor pressure vessel beltline materials is currently evaluated using U.S. Nuclear Regulatory Commission Regulatory Guide 1.99 Revision 2 (RG1.99/2), which presents methods for estimating the shift in Charpy transition temperature at 30 ft-lb (TTS) and the drop in Charpy upper shelf energy (ΔUSE). The purpose of the work reported here is to improve on the TTS correlation in RG1.99/2 using the broader database now available and current understanding of embrittlement mechanisms.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 14 publications
2
71
0
Order By: Relevance
“…For example, a rapid increase, followed by saturation, followed by slow coarsening and a decrease in number density of precipitates was predicted by models and confirmed experimentally for 0.3% Cu RPV steels irradiated at low neutron flux and 290°C [13]. As another example, it has been shown that an increase in the nickel content in irradiated RPV material correlates to an increase in both average radius and number density of copper-rich precipitates [16]. Further, changes in the irradiation temperature particularly in the range of about 250-300°C, as well as the neutron flux has been shown to strongly affect how the microstructure evolves over increasing neutron fluence [13,17,18].…”
Section: Integrate Sensing Modeling and Uncertainty For Remaining LImentioning
confidence: 58%
See 1 more Smart Citation
“…For example, a rapid increase, followed by saturation, followed by slow coarsening and a decrease in number density of precipitates was predicted by models and confirmed experimentally for 0.3% Cu RPV steels irradiated at low neutron flux and 290°C [13]. As another example, it has been shown that an increase in the nickel content in irradiated RPV material correlates to an increase in both average radius and number density of copper-rich precipitates [16]. Further, changes in the irradiation temperature particularly in the range of about 250-300°C, as well as the neutron flux has been shown to strongly affect how the microstructure evolves over increasing neutron fluence [13,17,18].…”
Section: Integrate Sensing Modeling and Uncertainty For Remaining LImentioning
confidence: 58%
“…As another example, it has been shown that an increase in the nickel content in irradiated RPV material correlates to an increase in both average radius and number density of copper-rich precipitates [16]. Further, changes in the irradiation temperature particularly in the range of about 250-300°C, as well as the neutron flux has been shown to strongly affect how the microstructure evolves over increasing neutron fluence [13,17,18]. The following sections provide a discussion on other possible contributions of microstructural features to β, in terms of reported microstructural evolutions over the relevant irradiation conditions in the current study.…”
Section: Integrate Sensing Modeling and Uncertainty For Remaining LImentioning
confidence: 99%
“…It has been shown for a neutron flux above about 5x10 11 n/(cm 2 -s), the evolution of microstructural features is dependent on flux [6,22]. This effect can be approximated by the relation [22,23]: 2 1 r e t t (5) r is an arbitrary reference flux, and in this study was r = 2.8x10 12 n/(cm 2 -s). At the relatively high neutron fluxes of samples in this study, it has been shown that an increase in neutron flux produces an increase in the concentration of unstable matrix feature clusters [6,22].…”
Section: Materials Samplesmentioning
confidence: 62%
“…The number of reactors worldwide that have been in operation for about or more than 40 years is increasing. Surveillance data from these aged reactors indicate higher ductile brittle transition temperatures than those predicted by embrittlement correlation methods [1,2]. In particular, the precipitates are the main defect clusters, and only small quantities of loops were observed by transmission electron microscopy.…”
Section: Introductionmentioning
confidence: 78%